Processing GOTO data with the Rubin Observatory LSST Science Pipelines I: Production of coadded frames. (18th January 2021) - Mullaney, J. R.; Makrygianni, L.; Dhillon, V.; Littlefair, S.; Ackley, K.; Dyer, M.; Lyman, J.; Ulaczyk, K.; Cutter, R.; Mong, Y.-L.; Steeghs, D.; Galloway, D. K.; et al.
Abstract: The past few decades have seen the burgeoning of wide-field, high-cadence surveys, the most formidable of which will be the Legacy Survey of Space and Time (LSST) to be conducted by the Vera C. Rubin Observatory. So new is the field of systematic time-domain survey astronomy; however, that major scientific insights will continue to be obtained using smaller, more flexible systems than the LSST. One such example is the Gravitational-wave Optical Transient Observer (GOTO) whose primary science objective is the optical follow-up of gravitational wave events. The amount and rate of data production by GOTO and other wide-area, high-cadence surveys presents a significant challenge to data processing pipelines which need to operate in near-real time to fully exploit the time domain. In this study, we adapt the Rubin Observatory LSST Science Pipelines to process GOTO data, thereby exploring the feasibility of using this 'off-the-shelf' pipeline to process data from other wide-area, high-cadence surveys. In this paper, we describe how we use the LSST Science Pipelines to process raw GOTO frames to ultimately produce calibrated coadded images and photometric source catalogues. After comparing the measured astrometry and photometry to those of matched sources from PanSTARRS DR1, we find that measured source positions are typically accurate to subpixel levels, and that measured L -band photometries are accurate to 50 mmag at m_L16 and 200 mmag at m_L18 . These values compare favourably to those obtained using GOTO's primary, in-house pipeline, gotophoto, in spite of both pipelines having undergone further development and improvement beyond the implementations used in this study. Finally, we release a generic 'obs package' that others can build upon, should they wish to use the LSST Science Pipelines to process data from other facilities.